UNIDROIT Principles in the system of unifi cation of international trade law (International relations and international law Journal, 2016)
The article analyzes the legal nature and importance of the Principles of International Commercial Contracts (UNIDROIT Principles) in the unification of international trade. Different points of view were expressed based on the research of opinions of scientists and experts in this field. Having examined the content of the UNIDROIT Principles in a generalized-complex form, the author formulated the appropriate conclusions and proposals. Study and application of the UNIDROIT Principles in Kazakhstan is necessary for the participants of the international trade and their practical application sometimes generates many problems. The UNIDROIT Principles are of great value when developing a national legislation, e.g. for improvement of Civil Law regulations of the Republic of Kazakhstan and development of regulatory framework for international commercial arbitration (court of referees). Taking into account use of multiple references to the Principles as a rationale for decisions made in judicial and court practices and agreements of contractual parties, they could be used by the arbitration courts of the Republic of Kazakhstan and Kazakhstans Chamber of Commerce and Industry.
Keywords: International Institute for the Unification of Private Law (UNIDROIT); Principles of International Commercial Contracts (UNIDROIT Principles); unification; international trade